2014
DOI: 10.1002/ijc.28998
|View full text |Cite
|
Sign up to set email alerts
|

HPV-avertable cancer risks in India: A pooled analysis of 9 observational studies

Abstract: Dear Sir, We read with great interest the article by Michaud et al. 1 "Highrisk HPV types and head and neck cancer." Their research presents the associations between infections with high-risk HPV subtypes and head and neck cancer risk in the US. In addition to HPV16, HPV18/33, and HPV52 emerged as important risk factors for oropharyngeal and oral cancers, respectively.Oral cancer is the most common form of malignant cancers in the Indian subcontinent; it accounts for one-third of the global burden of oral canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Alternative strategies such as naked eye visual inspection of cervix (down staging), visual inspection with acetic acid (VIA), magnified VIA (VIAM), visual inspection with lugol's iodine (VIAL), cervicography and HPV DNA testing in detecting cervical cancer and its precursors have to be adopted [33]. Regular screening through VIA has along with further referral for treatment has been suggested in a pooled analysis [34]. As the age affected by cervical cancer is decreasing thus a study has suggested that screening should be initiated at 25 years of age [19].…”
Section: Recommendations-need Of the Hourmentioning
confidence: 99%
“…Alternative strategies such as naked eye visual inspection of cervix (down staging), visual inspection with acetic acid (VIA), magnified VIA (VIAM), visual inspection with lugol's iodine (VIAL), cervicography and HPV DNA testing in detecting cervical cancer and its precursors have to be adopted [33]. Regular screening through VIA has along with further referral for treatment has been suggested in a pooled analysis [34]. As the age affected by cervical cancer is decreasing thus a study has suggested that screening should be initiated at 25 years of age [19].…”
Section: Recommendations-need Of the Hourmentioning
confidence: 99%